Diffusivities in Binary and Ternary Mixtures Containing Poly(ethylene) Glycol, Acetonitrile, and Water by Dynamic Light Scattering - Chittem, Pranay Kumar; Supper, Malvina; Kaspereit, Malte; Wu, Wenchang; Fröba, Andreas Paul (Industrial & Engineering Chemistry Research, 2024)
In the present study, one of the eigenvalues D̂1 of the Fick diffusion matrix for ternary mixtures consisting of polydisperse poly(ethylene) glycol (PEG), acetonitrile, and water as well as the mutual diffusivity D11 in two binary subsystems were determined by dynamic light scattering. PEGs with molecular weights Mn ranging from (400 to 4000) g·mol-1, a solvent mixture containing acetonitrile, and an experimental temperature of 323 K were selected because of their relevance to the application of reversed-phase liquid chromatography. In general, the accessed D̂1 decreases with increasing Mn and presents different concentration dependences. It was demonstrated that the accessed D̂1 is associated with the diffusion of PEGs in the solvent mixture and can be considered as the self-diffusivity of the sphere-like PEG molecules in the vicinity of infinite dilution regime. Using the self-diffusivity and the dynamic viscosity of the solvent mixture, the hydrodynamic diameter of the PEG molecules was determined via the Stokes-Einstein relation. While the values match that determined in water for smaller Mn, they tend to be smaller than that in water for larger Mn. This indicates a minor influence of the solvent or temperature on the hydrodynamic diameter of the PEG molecules. The determined diffusivities and hydrodynamic diameters of PEGs under process-relevant conditions are of relevance for the development of chromatographic separations.
CRIS-Team Scopus Importer:2024-08-16